DMF as an amine source: iron-catalyzed cyclization of 2H-azirines to imidazoles - Zhao, Mi-Na; Yang, Zi-Mo; Li, Lian-Qing (Chemical communications (Cambridge, England), 2024)
A novel method has been developed for the synthesis of 1-methyl4,5-diaryl-1H-imidazoles through Fe(II)-catalyzed cyclization of 2H-azirines and N,N-dimethylformamide (DMF) as an amine source. This transformation involves the cleavage of C-N and C=N double bonds and the construction of new C-N and C=N double bonds. The reaction has readily available starting materials, a wide range of substrates and mild reaction conditions. In addition, the reaction also facilitated the convenient synthesis of 1-methyl-2,4,5-triaryl1H-imidazoles.